Dominica : OECS Fiscal Issues, Policies to Achieve Fiscal Sustainability and Improve Efficiency and Equity of Public Expenditures - World Bank (Washington, DC, 2012)
This report concludes that during FY1993/94 to FY002/03 the fiscal policy implemented by the government of Dominica was unsustainable and posed a risk to the stability of the currency board arrangement. Moreover, this report recommends that most of the adjustment required to achieve a sustainable fiscal policy needed to come from expenditure cuts, in particular a reduction in the number of established and non-established positions, and from focusing capital expenditures on projects geared to growth and poverty reduction and funded largely by grants and concessional loan. A reduction in tax exemptions and discretionary concessions is also essential, as is a restructuring of the revenue base through the introduction of the value-added tax (VAT). While social indicators are good for a country at this level of gross domestic product (GDP), there is ample room for more efficient modalities of education and health service delivery that can generate significant savings and improve effectiveness. In addition, the government should strive to ensure that its social programs, in particular social protection, are delivered in a well-targeted and effective manner in order to provide more effective safety nets in the context of fiscal consolidation and continued vulnerability to external shocks. The report is organized as follows: Chapter 1 discusses fiscal sustainability in Dominica and presents options for fiscal consolidation; Chapter 2 discusses the budget management system in place and its effect on budgetary outcomes. Chapter 3 examines the Public Sector Investment Program (PSIP); Chapter 4 discusses public sector employment and compensation; Chapters 5 and 6 examine public expenditures and outcomes in the health and education sectors; and Chapter 7 discusses social protection programs.